Anatomical and Functional Outcomes of Human-Amniotic Membrane Graft in Refractory Macular Hole Cases - Soefiandi Soedarman; Sandi Muslim; Waldensius Girsang; Elvioza; Referano Agustiawan; Alberthus Donni Budi Prasetya; Ichsan Fauzi Triyoga (Vision)
Macular hole (MH) surgery generally has a high success rate, but finding anatomical plug for refractory cases remains challenging. The human amniotic membrane (hAM), with its anti-inflammatory and regenerative properties, has emerged as a potential option. This study aims to report the anatomical and functional outcomes of human amniotic membrane (hAM) graft as an intervention to repair refractory macular hole cases where wide internal limiting membrane (ILM) peeling was unsuccessful. A retrospective chart review was conducted at a single center, with the main outcomes being closure rate and postoperative BCVA at 6 months. Eleven eyes of 11 patients with refractory macular holes were identified and included in the study. Participants were predominantly males (72.73%) with a mean age of 49.27 years. Nine eyes achieved successful MH closure with a single intervention and showed no recurrence during the 6-month follow-up. Mean BCVA at 3 and 6 months improved significantly (p = 0.0207) from 1.747 ± 0.74 logMAR to 1.210 ± 0.51 logMAR and 0.939 ± 0.47 logMAR (range 2.079–0.301 logMAR). The use of human amniotic membrane (hAM) graft seems to be a viable and effective alternative for the treatment of refractory macular holes. However, further larger prospective controlled studies are necessary to confirm our results.